Droplet friction nano-generator and preparation method thereof
By doping BaTiO3 in PDMS and spraying PTFE, the problems of charge dissipation and output reduction of single-droplet friction nanogenerators in humid environments are solved, and high-performance power generation in high-humidity environments are achieved.
Patent Information
- Application Number
- CN202411779425.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
Single droplet friction nanogenerators exhibit rapid charge dissipation and reduced output voltage in humid environments, limiting their application in high humidity or liquid environments.
The friction charge transfer process is optimized by doping the high dielectric constant material BaTiO3 in PDMS and spraying the strong electronegative material PTFE on the surface, forming a coating to enhance charge polarization and contact sites.
It achieves good power generation performance in high humidity environments, with the open circuit voltage and output charge generated by a single droplet reaching 230V and 315nC, and still retains 90% of the initial electrical output in a high humidity environment of 90% RH.
Smart Images

Figure CN119582641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a micro-nano generator and a manufacturing method thereof, and specifically to a droplet friction nanogenerator and a manufacturing method thereof. Background Art
[0002] As an emerging energy harvesting technology, single droplet triboelectric nanogenerators (LD-TENGs) have attracted extensive attention due to their low cost, high efficiency and sustainability. The technology uses the friction interaction between droplets and material surfaces to convert mechanical energy into electrical energy to provide energy for microelectronic devices, wearable devices and smart sensors. However, although LD-TENGs show significant voltage output in dry environments, their performance in wet environments faces multiple challenges, especially the rapid dissipation of charge and the significant reduction in output voltage, which is particularly significant in high humidity or liquid environments. The presence of moisture often causes charge leakage and charge transfer on the friction surface, reducing the charge storage efficiency of the nanogenerator and thus limiting its performance. This charge dissipation phenomenon is one of the key factors that restrict the performance of single droplet triboelectric nanogenerators. Moisture or water has a significant impact on the triboelectric effect, resulting in unstable voltage output, which further limits its reliability and effectiveness in practical applications.
[0003] To address the above problems, researchers have proposed a variety of improvement strategies. For example, physical encapsulation methods effectively prevent moisture intrusion, thereby protecting the internal structure and charge of the friction nanogenerator and extending its service life. However, the increase in encapsulation materials may lead to an increase in the volume and weight of the friction nanogenerator, thereby affecting its flexibility and application range. Another water-assisted method uses the interaction between water and polymer triboelectric materials to increase the surface charge density and slow down the charge dissipation problem caused by moisture, but this method may not provide sufficient mechanical strength to meet the requirements of the friction nanogenerator in terms of robustness and wear resistance.
[0004] In recent years, superhydrophobic triboelectric materials have shown unparalleled advantages in the field of advanced triboelectric materials due to their unique hydrophobic properties, excellent moisture resistance and excellent electrical properties. The main construction strategies of superhydrophobic materials include molecular design, component regulation and surface microstructure customization, which can significantly reduce the impact of moisture on charge and thus improve output performance. However, how to maintain the stability and durability of materials in high humidity environments remains a major challenge. For example, specific molecular structures may hydrolyze or degrade under the action of moisture, affecting the long-term stability of the material; and compatibility issues between materials may also lead to a reduction in overall performance. In addition, uneven microstructures may cause the rupture of the air layer, reduce hydrophobicity, and lead to instability in contact area and friction, ultimately leading to uneven charge distribution and affecting triboelectric output efficiency. Summary of the invention
[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a high-performance, high-humidity resistant droplet friction nanogenerator. Another purpose of the present invention is to provide a droplet friction nanogenerator with good mechanical durability and acid and alkali corrosion resistance.
[0006] Technical solution: The method for preparing a droplet friction nanogenerator described in the present invention comprises the following steps:
[0007] Step 1: Mix PDMS and a curing agent to prepare a PDMS solution; mix PTFE particles with ethanol and disperse them by ultrasonic to obtain a PTFE suspension;
[0008] Step 2, mixing BaTiO3 (BTO) particles with PDMS solution, and ultrasonically dispersing them to obtain a mixture;
[0009] Step 3, applying the mixture on the surface of the substrate, evacuating the mixture, and drying and pre-curing the mixture;
[0010] Step 4, spraying the PTFE suspension on the surface of the product obtained in step 3, drying and curing to form a coating on the surface of the substrate;
[0011] Step five, arrange the top electrode in the middle position of the surface of the product obtained in step four to obtain a droplet friction nanogenerator.
[0012] Furthermore, in step 1, the curing agent is any one of dibutyl phthalate and dibutyltin dilaurate, and the mass ratio of PDMS to the curing agent is 8 to 12: 1. The diameter of the PTFE particles is 2 to 10 μm, preferably 3 μm, and the mass fraction of the PTFE particles in the suspension is 5 to 20 wt%.
[0013] Furthermore, in step 2, the average particle size of the BaTiO3 particles is 50 to 500 nm, preferably 100 nm, the dielectric constant is 120, and the mass fraction of the BaTiO3 particles in the mixture is 10 to 25 wt%, preferably 20 wt%.
[0014] Furthermore, the temperature of ultrasonic dispersion is 10-30° C., the frequency is 20-60 kHz, and the power is 60-120W.
[0015] Furthermore, in step 3, the substrate is one of a PET film, a PVC film or an ITO conductive film. The pressure after vacuuming is 0.04-0.08 MPa, and the drying pre-curing temperature is 55-65° C. for 10-15 min.
[0016] Furthermore, in step 4, the temperature of drying and curing is 55-65°C, the time is 2h-4h, the thickness of the coating is 150-300 μm, and the spraying volume is more than 2 ml.
[0017] Furthermore, in step five, the top electrode is any one of a conductive copper wire, a conductive silver wire, and a tinned copper wire, with a diameter of 0.8 to 1.2 mm and a length of 10 to 30 mm.
[0018] The droplet friction nanogenerator obtained by the preparation method of the droplet friction nanogenerator described in the present invention comprises a substrate, a coating is arranged on the surface of the substrate, and a top electrode is arranged on the surface of the coating; the coating is made of BaTiO3, PDMS and PTFE.
[0019] Preparation principle: By doping PDMS with high dielectric constant material BaTiO3, charge polarization can be effectively enhanced, triboelectric charge storage capacity can be improved, and charge dissipation can be reduced. At the same time, the surface spraying of strong electronegative material PTFE increases the charge contact sites, thereby optimizing the triboelectric charge transfer process and generating more triboelectric charges. Under the synergistic effect of charge storage enhancement and charge transfer optimization, the output performance of TENG is enhanced, such as Figure 1 At the same time, the PTFE particles sprayed during pre-curing are firmly embedded in the surface of the triboelectric material, forming a uniform micro-nano structure, which gives it stable super-hydrophobic and low-adhesion properties, and can effectively prevent the surface charge dissipation caused by moisture in the air in a high-humidity environment, avoiding the reduction of the output performance of the triboelectric nanogenerator.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0021] 1. By doping BaTiO3 and spraying PTFE, a droplet friction nanogenerator with excellent power generation effect was prepared. The open circuit voltage and output charge generated by a single droplet reached 230V and 315nC respectively;
[0022] 2. The PTFE particles sprayed on the surface give the triboelectric material super-hydrophobic and low-adhesion properties, making the droplet friction nanogenerator exhibit excellent moisture resistance. In a high humidity environment of 90% RH, 90% of the initial electrical output is still retained, and the open circuit voltage and output charge are as high as 207V and 285nC;
[0023] 3. The super-hydrophobic surface prepared by pre-curing spraying has excellent mechanical durability and acid and alkali corrosion resistance. After sandpaper wear, scratching and acid and alkali corrosion, it still has good super-hydrophobicity. This also makes the moisture resistance of the droplet friction nanogenerator not significantly degraded after the above damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the principle of the present invention;
[0025] Figure 2 It is a schematic diagram of the structure of the present invention;
[0026] Figure 3 is a schematic diagram of the structure of the coating 2 of the present invention;
[0027] Figure 4 This is an open circuit voltage effect diagram of the droplet friction nanogenerator with different BTO doping concentrations of the present invention;
[0028] Figure 5 It is a short-circuit current effect diagram of the droplet friction nanogenerator with different BTO doping concentrations of the present invention;
[0029] Figure 6 This is a diagram showing the output charge effect of the droplet friction nanogenerator with different BTO doping concentrations of the present invention;
[0030] Figure 7 is a surface SEM image of Comparative Example 1 of the present invention;
[0031] Figure 8 is a contact angle diagram of Comparative Example 1 of the present invention;
[0032] Fig. 9 This is an open circuit voltage effect diagram of the droplet friction nanogenerator with different PTFE spraying concentrations of the present invention;
[0033] Fig.10 This is a short-circuit current effect diagram of the droplet friction nanogenerator with different PTFE spraying concentrations of the present invention;
[0034] Fig.11 This is a graph showing the output charge effects of the droplet friction nanogenerator with different PTFE spraying concentrations of the present invention;
[0035] Fig.12 is a surface SEM image of Example 7 of the present invention;
[0036] Fig.13 is a contact angle diagram of Example 7 of the present invention;
[0037] Fig.14 is a rolling angle diagram of embodiment 7 of the present invention;
[0038] Fig.15 The power generation effect diagram of the droplet friction nanogenerator at different humidity before and after spraying in Test Example 1 of the present invention, wherein (a) after spraying, (b) before spraying;
[0039] Fig.16 is a contact angle variation diagram of sandpaper wear in Test Example 2 of the present invention;
[0040] Fig.17This is a diagram showing the power generation effects after different surface treatments in Test Example 2 of the present invention;
[0041] Fig.18 1 is a graph showing the contact angle changes at different pH values in Test Example 2 of the present invention, wherein (a) pH=14, (b) pH=7, and (c) pH=2;
[0042] Fig.19 This is a diagram of power generation effects after different pH values in Test Example 2 of the present invention;
[0043] Fig. 20 The open circuit voltage effect diagram at different humidity after mechanical damage and acid-base corrosion in Test Example 3 of the present invention, wherein (a) after mechanical damage, (b) after acid-base corrosion;
[0044] Fig.21 This is a voltage diagram of continuous long-time power generation in Test Example 4 of the present invention;
[0045] Fig. 22 is the contact angle diagram in Test Example 4 of the present invention;
[0046] Fig.23 This is a diagram showing the change in the generated voltage after being placed for different days in Test Example 4 of the present invention;
[0047] Fig.24 This is a diagram showing the power generation effect when the FEP suspension is sprayed in Comparative Example 2 of the present invention;
[0048] Fig.25 is the open circuit voltage when other nanoparticles are doped in Comparative Example 3 of the present invention;
[0049] Fig.26 This is a surface contact angle picture of comparative example 4 of the present invention when PVA is used as the matrix. DETAILED DESCRIPTION
[0050] Unless otherwise specified, the materials, reagents, instruments, etc. used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0051] Example 1
[0052] A method for preparing a droplet friction nanogenerator comprises the following steps:
[0053] (1) PDMS and curing agent dibutyl phthalate were mixed in a mass ratio of 10:1 to prepare a PDMS solution. PTFE particles with an average particle size of 3 μm were mixed with ethanol, and ultrasonically dispersed at 20° C. for 20 min, with an ultrasonic frequency of 40 KHz and an ultrasonic power of 100 W to obtain a PTFE suspension with a mass fraction of 15 wt%.
[0054] (2) BTO particles with an average particle size of 100 nm were mixed with a PDMS solution, with a BTO mass fraction of 10 wt %, and ultrasonic dispersion was performed respectively at an ultrasonic temperature of 20° C., an ultrasonic time of 5 min, an ultrasonic frequency of 40 KHz, and an output power of 100 W to obtain a mixture.
[0055] (3) Take 5 ml of the mixture obtained in step (2) and apply it on the surface of an ITO conductive film with a size of 30 mm x 60 mm x 0.125 mm, then evacuate at a pressure of 0.08 MPa for 20 min and dry at 60° C. for 12 min to solidify.
[0056] (4) Spray 5 ml of PTFE suspension onto the surface of the product obtained in step (3), dry and solidify at 60° C. for 3 h, and form a coating 2 with a thickness of 200 μm on the surface of the ITO conductive film substrate 1.
[0057] (4) A tinned copper wire with a diameter of 1.2 mm and a length of 30 mm was arranged in the middle position of the surface of the four samples obtained in step (3) as the top electrode 3 to obtain four groups of droplet friction nanogenerators.
[0058] like Figures 2-3 In the droplet friction nanogenerator obtained in this embodiment, there is a coating 2 on the ITO conductive film substrate 1, the PTFE of the coating 2 is embedded in the BTO-PDMS surface, and there is a top electrode 3 in the center of the surface of the coating 2.
[0059] Example 2
[0060] The remaining steps of this embodiment are the same as those of embodiment 1, with the only difference being that in step (2), the mass fraction of BTO is 15 wt%.
[0061] Example 3
[0062] The remaining steps of this embodiment are the same as those of embodiment 1, with the only difference being that in step (2), the mass fraction of BTO is 20 wt%.
[0063] Example 4
[0064] The remaining steps of this embodiment are the same as those of embodiment 1, with the only difference being that in step (2), the mass fraction of BTO is 25 wt%.
[0065] The power generation effects of the friction nanogenerators obtained in Examples 1 to 4 were measured respectively, and the results are as follows: Figures 4 to 6As shown. As the BTO mass fraction increases from 10% to 20%, the output charge of the droplet friction nanogenerator increases from 59nC to 88nC, an increase of about 1.5 times. At the same time, the open circuit voltage and short circuit current increase from 51V and 190nA to 71V and 226nA, respectively, thanks to the doping of BTO and its uniform dispersion. The doped BTO effectively improves the relative dielectric constant of the material and gives it a stronger charge polarization ability, thereby storing more charge during the friction process, reducing charge dissipation, and then converting it into higher output. As the mass fraction of BTO further increases to 25%, the output performance of TENG remains basically unchanged. This may be because excessive doping of BTO leads to uneven dispersion in the triboelectric material, agglomeration, and the relative dielectric constant of the material cannot be effectively improved, and the output charge of TENG is not further improved. It can be seen that the optimal mass percentage of BTO is 20wt%.
[0066] Comparative Example 1
[0067] The remaining steps of this comparative example are the same as those of Example 3, except that step (4) is omitted and the pre-curing time of step (3) is replaced by 3 hours. The surface morphology is observed by cold field scanning electron microscopy (SEM) and the contact angle is tested. The results are as follows: Figure 7 As shown. After doping, the surface of the triboelectric material is exposed to uniformly distributed BTO particles with a diameter of about 100nm, which shows that the high dielectric constant material is successfully introduced into the friction layer, which is beneficial to increase the number of polarized charges and improve the output performance of the droplet friction nanogenerator. Figure 8 However, due to the insufficiently significant micro-nanostructure produced by the BTO particles on the surface and the inherent hydrophilicity of BTO, the contact angle of the sample was only 116°, which did not reach superhydrophobicity and could not improve the moisture resistance of the droplet friction nanogenerator.
[0068] Example 5
[0069] A method for preparing a droplet friction nanogenerator comprises the following steps:
[0070] (1) PDMS and dibutyl phthalate were mixed in a mass ratio of 10:1 to prepare a PDMS solution. PTFE particles with an average particle size of 3 μm were mixed with ethanol, and the PTFE mass fraction was 5 wt %. The four groups of mixtures were then ultrasonically dispersed at an ultrasonic temperature of 20° C., an ultrasonic time of 20 min, an ultrasonic frequency of 40 kHz, and an output power of 100 W to obtain a PTFE suspension.
[0071] (2) BTO particles with a diameter of 100 nm were mixed with PDMS solution in different proportions, wherein the mass fraction of BTO was 20 wt %, and then ultrasonic dispersion was performed at an ultrasonic temperature of 20° C., an ultrasonic time of 5 min, an ultrasonic frequency of 40 KHz, and an output power of 100 W to obtain a mixture.
[0072] (3) Take 5 ml of the mixture obtained in step (2) and apply it on the surface of an ITO conductive film with a size of 30 mm x 60 mm x 0.125 mm, then evacuate at a pressure of 0.08 MPa for 15 min and pre-cure at 60° C. for 12 min.
[0073] (4) Take 5 ml of the four groups of suspensions in step (3) and spray them on the pre-cured surface in step (3) respectively, dry them at 60°C for 3 hours and solidify them to obtain four groups of samples, wherein the coating thickness is about 200 μm.
[0074] (5) A tinned copper wire with a diameter of 1.2 mm and a length of 30 mm was arranged in the middle position of the surface of the four samples obtained in step (4) as the top electrode 3 to obtain four groups of droplet friction nanogenerators.
[0075] Example 6
[0076] The remaining steps of this embodiment are the same as those of embodiment 5, with the only difference being that in step (1), the mass fraction of PTFE is 10 wt %.
[0077] Example 7
[0078] The remaining steps of this embodiment are the same as those of embodiment 5, with the only difference being that in step (1), the mass fraction of PTFE is 15 wt %.
[0079] Example 8
[0080] The remaining steps of this embodiment are the same as those of embodiment 5, with the only difference being that in step (1), the mass fraction of PTFE is 20 wt %.
[0081] The power generation effects of the friction nanogenerators obtained in Examples 5 to 8 were measured respectively, and the results are as follows: Figures 9-11As shown. With the continuous increase of the concentration of sprayed PTFE particles, the output charge continues to increase. When the mass fraction reaches 15%, the output charge increases from 145nC to 315nC, an increase of 217%, and an increase of 358% compared with before spraying. At the same time, the open circuit voltage and short circuit current also increase from 110V and 340nA to 230V and 420nA, an increase of 209% and 123% respectively. This is because with the increase of spraying concentration, more PTFE particles are embedded on the surface of the triboelectric material, increasing the triboelectric contact sites. At the same time, the surface fluorine content increases, generating more transfer charges, and then generating higher output charges. When the spraying concentration continues to increase to 20%wt, the output charge decreases, which can be explained by the uniformity of the surface particle dispersion. With the further increase of the concentration of surface sprayed PTFE particles, although the fluorine content on the surface of the triboelectric material increases, the particles cover each other, and the solid-liquid contact sites decrease during the friction process, resulting in a decrease in transfer charge and a decrease in output charge.
[0082] The surface morphology of the droplet friction nanogenerator prepared with a PTFE mass fraction of 15wt% was observed by cold field scanning electron microscopy. Fig.12 As shown. After spraying, PTFE is evenly embedded on the surface, and the particle diameter is <5μm. This helps the strongly electronegative PTFE to participate in friction charging during the friction process and increase the amount of friction charge transfer. The semi-cured spraying process in this article utilizes the liquid properties of PDMS in a semi-cured state. On the one hand, PTFE particles can settle on the surface of the semi-cured state and be embedded in the surface after curing; on the other hand, semi-cured PDMS acts as a binder to form a bonding bridge between different PTFE particles. At the same time, the sprayed PTFE particles construct a significant micro-nano structure on the surface, giving the friction layer super-hydrophobic and low-adhesion properties, such as Figures 13-14 , the contact angle is as high as 164° and the rolling angle is as low as 3°, which helps to enhance the moisture resistance of the droplet triboelectric nanogenerator. The optimal mass fraction of PTFE is 15wt%.
[0083] Test Example 1
[0084] In order to verify that the droplet friction nanogenerator of the present invention maintains a good power generation effect in a high humidity environment, the samples obtained in Comparative Example 1 and Example 7 were used to test the power generation effect under different environmental relative humidity (RH), specifically 50% RH, 60% RH, 70% RH, 80% RH, and 90% RH.
[0085] The results are as follows Fig.15As shown in the figure, when the relative humidity increases from 50% to 90%, the output voltage and charge of the unsprayed sample drop sharply by about 60%. In contrast, the open circuit voltage, short circuit current and output charge of the sample manufactured after spraying are slightly reduced, and about 90% of the initial electrical output is still retained at a relative humidity of 90%, up to 207V, 404nA and 285nC. It shows that the invented droplet friction nanogenerator has excellent moisture resistance. This is because the sprayed PTFE particles construct a uniform micro-nano structure on the surface of the friction layer, giving it super-hydrophobic and low-adhesion properties. In a high humidity environment, it can effectively repel moisture to ensure surface dryness, reduce charge dissipation, and reduce the impact of high humidity environment on TENG output performance.
[0086] Test Example 2
[0087] In order to verify the mechanical durability and chemical corrosion resistance of the surface spraying structure of the present invention, the samples obtained in Example 7 were used to conduct sandpaper wear, scratching and acid-base corrosion experiments, and the contact angle change and power generation effect were measured.
[0088] The results are as follows Fig.16 As shown in the figure, as the number of friction cycles increases, the contact angle decreases gradually and remains above 155° after 34 cycles, and the rolling angle rises to 6°. This is because during the friction process, the shallower particles embedded in the surface fall off first, protecting the deeper particles. At the same time, the deeper particles are firmly embedded in the coating and are not easy to fall off, which makes the contact angle decrease slowly in the later friction. The output performance of TENG after sandpaper wear and tool scratching was tested, as shown in Figure 1. Fig.17 As shown, the output voltage is 160V after sandpaper wear, and the output voltage is 200V after tool scratching, and a high power generation effect is still retained, which proves the mechanical stability of the surface embedded PTFE particles.
[0089] The sample was immersed in HCl solution (pH = 2), deionized water and NaOH solution (pH = 14), and the contact angle change process was measured as follows: Fig.18 As shown in the figure, the contact angle decreases slightly with the increase of immersion time. After immersion in strong alkali for 60 hours and in strong acid for 86 hours, the contact angle remains above 148°. The output performance of the triboelectric material after corrosion is tested, as shown in the figure. Fig.19 As shown in the figure, after acid and alkali corrosion, the output charge is 180V and 170V respectively, still showing excellent output performance, which is inseparable from the functional embedding of PTFE particles. It is precisely because of the chemical inertness of PTFE and its uniform dispersion on the surface that the triboelectric material has excellent corrosion resistance. In general, these robustness tests demonstrate the adaptability of TENG to various damages that may be encountered in energy harvesting applications.
[0090] Test Example 3
[0091] In order to verify that the surface of the droplet friction nanogenerator of the present invention still maintains good moisture resistance after being damaged, the sample after mechanical damage and acid and alkali corrosion in Test Example 2 was used to test the power generation effect under different relative humidity (RH), specifically 50% RH, 60% RH, 70% RH, 80% RH, and 90% RH. The results are as follows: Fig. 20 As shown, after the triboelectric material was mechanically and chemically damaged, it still exhibited excellent moisture resistance. Even in a high humidity environment of 90% RH, the output performance decreased by no more than 20%, demonstrating the potential to work in extremely harsh environments.
[0092] Test Example 4
[0093] The samples obtained in Example 7 were used to conduct continuous long-term power generation and power generation tests for different days to verify the durability and stability of the droplet friction nanogenerator. The results are as follows: Figures 21 to 23 As shown. It can be seen that: in more than 6300 droplet friction tests, the output voltage remained basically stable, and the contact angle at the droplet impact was still more than 155°, proving the durability of the surface mosaic structure. At the same time, even after being placed for 12 days, the CS-TENG can still stably output a voltage of 195V. This high stability shows that the CS-TENG has broad application prospects in practical applications.
[0094] Example 9
[0095] A method for preparing a droplet friction nanogenerator comprises the following steps:
[0096] (1) PDMS and curing agent dibutyltin dilaurate were mixed in a mass ratio of 8:1 to prepare a PDMS solution. PTFE particles with an average particle size of 3 μm were mixed with ethanol, and ultrasonically dispersed at 10° C. for 20 min, with an ultrasonic frequency of 20 KHz and an ultrasonic power of 60 W to obtain a PTFE suspension with a mass fraction of 8 wt%.
[0097] (2) BTO particles with an average particle size of 50 nm were mixed with the PDMS solution, and ultrasonic dispersion was performed at 10° C. for 5 min, with an ultrasonic frequency of 20 kHz and an ultrasonic power of 60 W to obtain a mixture in which the mass fraction of the BTO particles was 16 wt %.
[0098] (3) The mixture was coated on the surface of the PET film substrate 1 by knife coating, and vacuumed at a pressure of 0.04 MPa for 20 min, and dried at 55° C. for pre-curing for 10 min.
[0099] (4) Spray 2 ml of PTFE suspension onto the surface of the product obtained in step (3), dry and solidify at 55° C. for 4 h, and form a coating 2 with a thickness of 150 μm on the surface of the substrate 1.
[0100] (5) Arrange a conductive copper wire with a diameter of 0.8 mm and a length of 10 mm as the top electrode 3 in the middle position of the surface of the object obtained in step (4) to obtain a droplet friction nanogenerator.
[0101] Example 10
[0102] A method for preparing a droplet friction nanogenerator comprises the following steps:
[0103] (1) PDMS and curing agent dibutyltin dilaurate were mixed in a mass ratio of 12:1 to prepare a PDMS solution. PTFE particles with an average particle size of 3 μm were mixed with ethanol, and ultrasonically dispersed at 30° C. for 20 min, with an ultrasonic frequency of 60 KHz and an ultrasonic power of 120 W to obtain a PTFE suspension with a mass fraction of 18 wt%.
[0104] (2) BTO particles with an average particle size of 500 nm were mixed with the PDMS solution, and ultrasonically dispersed at 30° C. for 5 min, with an ultrasonic frequency of 60 kHz and an ultrasonic power of 120 W to obtain a mixture in which the mass fraction of BTO particles was 23 wt %.
[0105] (3) The mixture was coated on the surface of the PVC film substrate 1 by knife coating, and vacuumed at a pressure of 0.06 MPa for 20 min, and dried at 65° C. for pre-curing for 15 min.
[0106] (4) Spray 4 ml of PTFE suspension onto the surface of the product obtained in step (3), dry and solidify at 65° C. for 2 h, and form a coating 2 with a thickness of 300 μm on the surface of the substrate 1.
[0107] (5) Arrange a conductive silver wire with a diameter of 1.0 mm and a length of 20 mm as the top electrode 3 in the middle position of the surface of the object obtained in step (4) to obtain a droplet friction nanogenerator.
[0108] Comparative Example 2
[0109] The remaining steps of this comparative example are the same as those of Example 7, except that the 15wt% PTFE suspension in step (1) is replaced by 15wt% poly(perfluoroethylene propylene) (FEP). Fig.24 As shown, the power generation effect is lower than that when spraying PTFE.
[0110] Comparative Example 3
[0111] The remaining steps of this comparative example are the same as those of Example 7, except that the BTO particles with an average particle size of 100 nm in step (2) are replaced with titanium dioxide (TiO2), aluminum oxide (Al2O3), and polyvinylidene fluoride (PVDF) particles with an average particle size of 100 nm. The results show that the power generation effect when doped with other nanoparticles is lower than that when doped with BTO. Fig.25 shown.
[0112] Comparative Example 4
[0113] The remaining steps of this comparative example are the same as those of Example 7, except that the PDMS (polydimethylsiloxane) in step (1) is replaced by PVA (polyvinyl alcohol). Fig.26 As shown, this easily causes moisture adhesion in a high humidity environment and cannot improve its moisture resistance.
[0114] In summary, the best embodiment is Embodiment 7.
Claims
1. A method for preparing a droplet friction nanogenerator, characterized in that: The following steps are involved: Step 1: Mix PDMS and a curing agent to prepare a PDMS solution; mix PTFE particles with ethanol and disperse them by ultrasonic to obtain a PTFE suspension; Step 2, mixing BaTiO3 particles with PDMS solution, and ultrasonically dispersing them to obtain a mixture; Step 3, applying the mixture on the surface of the substrate (1), evacuating the mixture, and drying and pre-curing the mixture; Step 4, spraying the PTFE suspension on the surface of the product obtained in step 3, drying and curing the product to form a coating (2) on the surface of the substrate; Step 5: Arrange a top electrode (3) at the middle position of the surface of the product obtained in step 4 to obtain a droplet friction nanogenerator.
2. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: In the step 1, the curing agent is any one of dibutyl phthalate and dibutyltin dilaurate, and the mass ratio of the PDMS to the curing agent is 8 to 12:
1.
3. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: In the step 1, the diameter of the PTFE particles is 2 to 10 μm, and the mass fraction of the PTFE particles in the suspension is 5 to 20 wt %.
4. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: In the step 2, the average particle size of the BaTiO3 particles is 50 to 500 nm, and the mass fraction of the BaTiO3 particles in the mixture is 10 to 25 wt%.
5. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: The temperature of the ultrasonic dispersion is 10-30° C., the frequency is 20-60 kHz, and the power is 60-120 W.
6. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: In the step three, the substrate (1) is one of a PET film, a PVC film or an ITO conductive film.
7. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: In the step three, the pressure after vacuuming is 0.04-0.08 MPa, the temperature of drying and pre-curing is 55-65° C., and the time is 10-15 min.
8. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: In the step 4, the temperature of the drying and curing molding is 55-65° C., the time is 2 h to 4 h, and the thickness of the coating (2) is 150-300 μm.
9. The method for preparing a droplet friction nanogenerator according to claim 1, characterized in that: In the step 5, the top electrode (3) is any one of a conductive copper wire, a conductive silver wire, and a tinned copper wire, with a diameter of 0.8 to 1.2 mm and a length of 10 to 30 mm.
10. A droplet friction nanogenerator obtained by the preparation method of a droplet friction nanogenerator according to any one of claims 1 to 9, characterized in that: The invention comprises a substrate (1), a coating (2) is arranged on the surface of the substrate (1), and a top electrode (3) is arranged on the surface of the coating (2); the coating (2) is made of BaTiO3, PDMS and PTFE.
Citation Information
Cited By
Performance-enhanced triboelectric fiber yarn with multi-structure design and preparation method of performance-enhanced triboelectric fiber yarn
CN120537064A